Performance of Soil Moisture Sensors in Florida Sandy Soils - Ferrarezi, Rhuanito Soranz; Rodrigues Nogueira, Thiago Assis [UNESP]; Cornejo Zepeda, Sara Gabriela (Mdpi, 2020)
Soil moisture sensors can improve water management efficiency by measuring soil volumetric water content (theta nu) in real time. Soil-specific calibration equations used to calculate theta nu can increase sensor accuracy. A laboratory study was conducted to evaluate the performance of several commercial sensors and to establish soil-specific calibration equations for different soil types. We tested five Florida sandy soils used for citrus production (Pineda, Riviera, Astatula, Candler, and Immokalee) divided into two depths (0.0-0.3 and 0.3-0.6 m). Readings were taken using twelve commercial sensors (CS650, CS616, CS655 (Campbell Scientific), GS3, 10HS, 5TE, GS1 (Meter), TDT-ACC-SEN-SDI, TDR315, TDR315S, TDR135L (Acclima), and Hydra Probe (Stevens)) connected to a datalogger (CR1000X; Campbell Scientific). Known amounts of water were added incrementally to obtain a broad range of theta nu Small 450 cm(3) samples were taken to determine the gravimetric water content and calculate the theta nu used to obtain the soil-specific calibration equations. Results indicated that factory-supplied calibration equations performed well for some sensors in sandy soils, especially 5TE, TDR315L, and GS1 (R-2 = 0.92) but not for others (10HS, GS3, and Hydra Probe). Soil -specific calibrations from this study resulted in accuracy expressed as root mean square error (RMSE) ranging from 0.018 to 0.030 m(3) m(-3) for 5TE, CS616, CS650, CS655, GS1, Hydra Probe, TDR310S, TDR315, TDR315L, and TDT-ACC-SEN-SDI, while lower accuracies were found for 10HS (0.129 m(3) m(-3)) and GS3 (0.054 m(3) m(-3)). This study provided soil -specific calibration equations to increase the accuracy of commercial soil moisture sensors to facilitate irrigation scheduling and water management in Florida sandy soils used for citrus production.
Keywords: bulk density; irrigation management; water loss reduction; volumetric water content